Effect of structure variations on the quadruplex DNA binding ability of nickel Schiff base complexes. Issue 38 (12th September 2018) - Davis, Kimberley J.; Assadawi, Nawal M. O.; Pham, Son Q. T.; Birrento, Monica L.; Richardson, Christopher; Beck, Jennifer L.; Willis, Anthony C.; Ralph, Stephen F.
Abstract : The synthesis of two new series of nickel complexes is described, along with their ability to bind to duplex and quadruplex DNA structures. Abstract : Two different series of nickel Schiff base complexes were prepared as part of a study aimed at discovering new compounds with high affinity and selectivity for quadruplex DNA (qDNA). The new complexes were prepared by modification of a literature method for synthesising N, N ′-bis-(4-((1-(2-ethyl)piperidine)-oxy)salicylidene)phenylenediaminenickel(ii ) (complex (1 )). For Series 1 complexes, the phenylenediamine head group of the literature complex was replaced with ethylenediamine, phenanthrenediamine, R, R - and S, S -diaminocyclohexane. These complexes, as well as an asymmetric molecule featuring a naphthalene moiety on one side and a single ethyl piperidinyl salicylidene group on the other, were prepared in order to examine the effect of varying the number and position of aromatic groups on DNA binding. Series 2 complexes were isomers of those in Series 1, in which pendant ethyl piperidine groups were located at different positions. All new complexes were characterised by 1D and 2D NMR spectroscopic methods alongside microanalysis and ESI-MS. In addition, the solid state structures of eight new complexes were determined using single crystal X-ray diffraction methods. N, N ′-Bis-(4-((1-(2-ethyl)piperidine)oxy)-salicylidine)diaminophenanthrenenickel(ii ) (9 ), was shown by ESI-MS, CD spectroscopy and UV melting studies to exhibit a greater affinity towards, and ability to stabilise, dsDNA than all other complexes in the first series. ESI-MS revealed (9 ) to have a strong tendency to form a 1 : 1 complex with the tetramolecular, parallel qDNA molecule Q4, however it exhibited low affinity towards the parallel unimolecular qDNA molecule Q1. The enantiomeric complexes (5 ) and (7 ), featuring R, R - and S, S -diaminocyclohexane moieties, respectively, showed similar binding profiles towards all DNA molecules investigated, whereas the asymmetric complex (11 ), exhibited very low DNA affinity in all cases. Series 2 complexes showed very similar DNA affinity and selectivity to their isomeric counterparts in Series 1. For example, (14 ) and (15 ), both of which contain a phenylenediamine head group, showed higher affinity towards D2, Q1 and Q4, than any of the other Series 2 complexes. In addition, complex (21 ), which contains a meso -1, 2-diphenylethylenediamine moiety, interacted strongly with Q4, but not D2 or Q1. This observation was very similar to that made previously for the isomeric complex (3 ).